Decreased Expression of the Aryl Hydrocarbon Receptor in Ocular Behcet's Disease. (22nd June 2014) - Wang, Chaokui; Ye, Zi; Kijlstra, Aize; Zhou, Yan; Yang, Peizeng
Abstract : Recent studies show that the aryl hydrocarbon receptor (AhR) is involved in immune responses. AhR is activated following interaction with its ligands, such as 6-formylindolo[3, 2-b]carbazole (FICZ) and 2-(1′H-indole-3′-carbonyl)-thiazole-4-carboxylic acid methyl ester (ITE). In this study, we investigated the role of AhR activation by its endogenous ligands in the pathogenesis of ocular Behcet's disease (BD). The expression of AhR was significantly decreased in active BD patients as compared to inactive BD patients and normal controls. Both FICZ and ITE inhibited Th1 and Th17 polarization and induced the expression of IL-22 by PBMCs and by CD4 + T cells in active BD patients and normal controls. Stimulation of purified CD4 + T cells with FICZ or ITE caused a decreased expression of RORC, IL-17, IL-23R, and CCR6 and an increased phosphorylation of STAT3 and STAT5. The present study suggests that a decreased AhR expression is associated with disease activity in BD patients. The activation of AhR by either FICZ or ITE was able to inhibit Th1 and Th17 cell polarization. Further studies are needed to investigate whether modulation of AhR might be used in the treatment of BD.